2015
DOI: 10.1071/ah14034
|View full text |Cite
|
Sign up to set email alerts
|

Managing ethical issues in patient care and the need for clinical ethics support

Abstract: Objective. To investigate the range, frequency and management of ethical issues encountered by clinicians working in hospitals in New South Wales (NSW), Australia.Methods. A cross-sectional survey was conducted of a convenience sample of 104 medical, nursing and allied health professionals in two NSW hospitals.Results. Some respondents did not provide data for some questions, therefore the denominator is less than 105 for some items. Sixty-two (62/104; 60%) respondents reported occasionally to often having eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Other participant groups were physicians (n = 172), 28,32,43,48 patients (n = 109), 43 nurse aids (n = 38), 48 nurse administrators (n = 32), 16 nurse educators (n = 11), 61 and combinations of nurses and social workers (n = 1215), 6 and nurses, allied health, and medical workers (n = 104). 49 In the latter two combined sample groups, the number of each participant group was not specified. One qualitative study reported no number of participants.…”
Section: Methodological Choices Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other participant groups were physicians (n = 172), 28,32,43,48 patients (n = 109), 43 nurse aids (n = 38), 48 nurse administrators (n = 32), 16 nurse educators (n = 11), 61 and combinations of nurses and social workers (n = 1215), 6 and nurses, allied health, and medical workers (n = 104). 49 In the latter two combined sample groups, the number of each participant group was not specified. One qualitative study reported no number of participants.…”
Section: Methodological Choices Of the Studiesmentioning
confidence: 99%
“…The development of an instrument Hospital Ethical Climate Survey (HECS) was the focus of one study 44 and evaluation of its psychometric properties was the focus of four studies. 44 47 Some of the studies evaluated healthcare organizations’ ethical climate in a one-site setting 48 –53 or compared ethical climate in different working environments. 18,54 56 Furthermore, two studies examined ethical climate by utilizing theoretical models 21,34 and promoting ethical climate was the focus area of two studies.…”
Section: Main Foci Of the Studiesmentioning
confidence: 99%
“…CES is defined as the formal or informal provision of advice and support to healthcare personnel on ethical issues arising from clinical practice and patient care within the healthcare setting (Owen 2001 ; Puntillo et al 2001 ; Slowther et al 2004a ). CES is becoming more prevalent with the increased awareness worldwide of the importance of ethical issues in healthcare and with personnel encountering an increasing number of ethical issues in clinical practice (Bartholdson et al 2015 ; Doran et al 2015 ; Oberle and Hughes 2001 ; Ulrich et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CES services must be accounted for in terms of efficiency and effectiveness. Consequently, one of the key questions is whether it is defensible to invest in and provide time-consuming CES services [38, 39]. While CES is reported to improve multidisciplinary team collaboration, working culture and quality of care [14, 34, 35, 3840], accountability of CES services in terms of efficiency and effectiveness remains complex.…”
Section: Discussionmentioning
confidence: 99%